Preliminary Calculation of the Energy Return on Investment (EROI) of Ecuadorian Oil (Aporte Santiaguino, 2020)
Ecuador in 1972 transformed its agricultural economy to one dependent on oil export earnings.However, a decrease is expected, exacerbated by a higher extraction energy cost. The energy rateof return (EROI), implies that the lower its value, the lower the net energy in favor of society.The methodology based on the David Murphy protocol was used as methodology. The objectiveof this investigation is to carry out a preliminary calculation of the EROI of Ecuadorian oil,at the country level and by blocks, obtaining preliminary EROI results for Blocks 7, 10, 15, 16,21, 46, 47, 56, 57, 60, 61, 62 and 67, and from Ecuador. It is verified that the EROI decreasesfrom a 43 : 1 to 27 : 1 ratio in twelve years, according to the API density and the percentageof BSW of the extracted crude oil that is higher. It is concluded that Ecuador, invests more andmore resources, especially fuel for electricity generation, in twelve years increased by 65 %.
Keywords: BSW; API density; Ecuador; EROI; Oil; Resources